Sentani Lake and The Papua Sea in Art: Representation, Abstraction, and Their Meaning in Papuan Society - Wicaksana, I Dewa Ketut; Rinantanti, Yulini (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2023)
This article investigates the representation of Sentani Lake and the Papua Sea in the traditional art of the Papuan people, aiming to uncover their cultural significance and implications. The study aims to identify the embedded meanings in artistic depictions of these natural elements and to understand how these representations reflect the cultural understanding and local wisdom of the Papuan community. Utilizing a qualitative approach, the study collects data from primary sources including cultural rituals, performing arts, and visual arts. Aesthetic theory is used to analyze the portrayal of the two bodies of water within the cultural context, while semiotic theory is applied to interpret the symbolic elements and socio-aesthetic meanings within the Sentani coastal culture. The research findings indicate that the artistic representation of Lake Sentani and the Papua Sea encompasses profound symbolic meanings beyond their visual depictions. These representations convey spiritual concepts, abundance, and the intricate relationship between humans and nature, reflecting a deep understanding of ecosystems and local beliefs. The article emphasizes the vital role of art in preserving the cultural and natural significance within the Papuan society, emphasizing the profound connections between humans. Sentani Lake, the Papua Sea, and their natural environment within the rich and diverse cultural context of Papua.